"Omics" and "epi-omics" underlying the β-cell adaptation to insulin resistance - Dario F. De Jesus; Rohit N. Kulkarni (Elsevier, 2019)
Background: Pancreatic β-cells adapt to high metabolic demand by expanding their β-cell mass and/or enhancing insulin secretion to maintain glucose homeostasis. Type 2 diabetes (T2D) is typically characterized by β-cell decompensation. Scope of the review: The current review focuses on summarizing the "omics" and "epi-omics" approaches that particularly focus on addressing the β-cell adaptation to insulin resistance and T2D. Major conclusions: The molecular mechanisms underlying successful versus compromised β-cell adaptation to insulin resistance are not entirely understood. The last decade has seen an exponential increase in the use of "omics" and "epi-omics" approaches to dissect pathophysiology of metabolic diseases. One recent example is the emergence of m6A mRNA methylation as a new layer of regulation of gene expression with the potential to impact diverse physiological processes in metabolic cells. Keywords: β-cells, Insulin resistance, Genomics, Transcriptomics, Epigenomics, Epitranscriptomics